Wallerian degeneration and peripheral nerve conditions for both axonal regeneration and neuropathic pain induction - Dubový, Petr (Annals of anatomy, 2011)
Wallerian degeneration is a cascade of stereotypical events in reaction to injury of nerve fibres. These events consist of cellular and molecular alterations, including macrophage invasion, activation of Schwann cells, as well as neurotrophin and cytokine upregulation. This review focuses on cellular and molecular changes distal to various types of peripheral nerve injury which simultaneously contribute to axonal regeneration and neuropathic pain induction. In addition to the stereotypical events of Wallerian degeneration, various types of nerve damage provide different conditions for both axonal regeneration and neuropathic pain induction. Wallerian degeneration of injured peripheral nerve is associated with an inflammatory response including rapid upregulation of the immune signal molecules like cytokines, chemokines and transcription factors with both beneficial and detrimental effects on nerve regeneration or neuropathic pain induction. A better understanding of the molecular interactions between the immune system and peripheral nerve injury would open the possibility for targeting these inflammatory mediators in therapeutic interventions. Understanding the pleiotropic effects of cytokines/chemokines, however, requires investigating their highly specific pathways and precise points of action.
Keywords: Models, Animal; Neurogenic Inflammation; regenerace nervu; Models, Neurological; Inflammation; Peripheral Nerve Injuries; modely neurologické; Peripheral Nerves; Neuralgia; zánět; axony; Wallerian Degeneration; Wallerova degenerace; Animals; lidé; buněčná imunita; Nerve Regeneration; Humans; poranění periferního nervu; zvířata; Immunity, Cellular; myši; modely u zvířat; Axons; Mice; neurogenní zánět; periferní nervy; neuralgie